W Gambaran Masalah Kesehatan Korban Pasca Bencana Gempa Cianjur - Wilda Fauzia; Imam Subiyanto; Reni Reni; Teti Hayati (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The impact of the disaster on the health problems of the post-earthquake victims in Cianjur can have direct or indirect consequences, namely due to the emergence of new health problems or due to previous co-morbidities. Many people have not been monitored for their health because they did not come to the nearest health post for check-ups. The purpose of this community service is to find out the post-earthquake public health problems in Cianjur. The method used was a survey and examination of health problems carried out in Wangun Village, Bone Kasih, Cianjur by lecturers and students of the Nursing Study Program, STIKes RSPAD Gatot Soebroto in collaboration with PMI. The program of activities carried out is to provide health services in the form of "door to door" health checks. Examination results of health problems such as headaches, stomach pain and joint pain are problems that many complain about. Based on the health problems experienced, many were caused by pre-existing diseases that were triggered by the earthquake and had not checked themselves into the nearest health post.